Bootstrapping the Cost Modelling of Hydropower Projects in Sub-Saharan Africa: Case of Chinese Financed Projects - Atchike, Desire Wade; Zhao, Zhen-Yu; Bao, Geriletu (International Journal of Energy Economics and Policy, 2020)
In last decades, many scholars have studied the cost of hydropower plants based on the capacity and head. The different correlation equations obtained depend mostly on geographical locations and electro-mechanical characteristics. As Sub-Saharan Africa remains the region with the largest untapped hydropower potential, coupled with the need of expansion of Chinese energy companies, this paper aims to estimate the cost of hydropower projects financed and constructed by Chinese companies in Sub-Saharan Africa. The data used in this study were rigorously selected. After refinement of the raw data, screening was performed to improve the quality of the database suitable for the log transformed linear regression. Furthermore, a bootstrap resampling with replacement was applied to assure the robustness of the model. The results show a good accuracy of the model confirmed by the high value of the coefficient of determination and an average error less than 20%. Keywords: Hydropower project cost, Capex modelling, bootstrap resampling, Sub-Saharan Africa, Chinese investment. JEL Classifications: A100, Q400, C390. DOI: https://doi.org/10.32479/ijeep.8842